Gross motor function in patients with cerebral palsy in rehabilitation process with virtual reality - Ide, Francisco Camolesi (2021)
Purpose: To verify whether there is a correlation between the variables of the interventions with Virtual Reality (VR) and if there is an influence (positive or negative) on motor function in people with Cerebral Palsy (CP). Methods: A systematic search was completed in PubMed; Web of Science; Scopus; Scielo and, Scholar Google (up to page 25). Applying selection criteria, 17 articles were selected. From the articles found, 145 individuals were analyzed concerning intervention variables. VR tools were classified as specific and non-specific. Statistical analysis determined variables' behavior through tests of multivariate analysis and the coefficient of correlation. Results: Non-specific hardware for rehabilitation programs presented better results and statistical results suggests a significant correlation between session time and improvement of motor function, pointing that sessions between 45 and 50 minutes are more efficient. Conclusions: Type of hardware and intervention time are significant when planning interventions for people with CP.